POSSIBILITY OF NEW SITES AS SOURCES OF INFECTION FOR MYCOPLASMA AGALACTIAE - A. Hasso , H. (The Iraqi Journal of Veterinary Medicine, 1994)
Conventionally reared goats and experimentally inoculated goats with Mycoplasma agalactiae were examined for the presence of M. agalactiae in their ears and nostrils. No isolates were obtained from the ears' of neither goats. An isolate. was obtained from the nostrils of a conventional goat, while the experimental goats yielded many isolates from their nostrils.